Land management education of Ukraine in conditions of eurointegration - Drebot, O.; Zubova, O.; Lukianenko, O.; Krasnolutsky, O. (Land Management, Cadastre and Land Monitoring, 2019)
The article deals with current problems of Eurointegration process in the field of land management education. The need for changes in the field of higher education in the process of teaching disciplines of land management specialities is proved, taking into account the importance of raising students’ knowledge level to develop a consciousness of the European values unity and provide future employment, including the European labor market. The purpose of the article is to develop approaches and principles of educational process, as well as the activities of higher educational institutions in general in order to increase the level of students’ knowledge and develop essential professional skills and social involvement in European processes in the field of land management. A method of scientific analysis, synthesis and generalization of current national and European approaches to teaching land management disciplines to students is used in the article. As a result of the research it was established that a comprehensive approach should be applied to teaching discipline. It includes introduction of new disciplines or subjects on European principles of land management into educational process; conducting scientific research in this area; cooperation with other educational institutions, and representatives of the StateGeoCadastre (Ukrainian land management state executive bodies), land management organizations; as well as free dissemination of scientific research. The material presented in this article is the foundation for organizing and improving the educational process in the field of land management education. Keywords. European integration and education, land management education, land management.